Analyzing the Impact of Corporate Social Responsibility on Brand Management for Start-Ups: Quantitative Research From Cyprus Businesses - Papa, Elena (My University, 2024)
In recent years, many businesses have adopted corporate social responsibility (CSR) to positively influence their macro and micro environment while building their competitive muscles. Many start-ups avoid adopting CSR, pointing to its high cost and invisible, short-term gains. As a result, this study aimed to establish the impact of CSR adoption on brand management. As a broad topic, the research focused on the five primary components of brand management: brand reputation, equity, loyalty, awareness, and recognition. The quantitative research narrowed down to test five hypotheses that sought to determine whether the adoption of CSR by start-ups positively affects brand reputation, equity, loyalty, awareness, and recognition. In completing the research, 228 participants (employees and customers) from 100 sampled Cyprus start-ups participated in answering closed-ended 30-item questionnaires categorized into six main items (CSR, brand reputation, equity, loyalty, awareness, and recognition), each of the five items. Cronbach’s alpha and Average Variance Extracted (AVE) were adopted as the primary tools to test the Reliability and validity of the test. The results indicated all five hypothesizes passed the confirmatory factor analysis (CFA) with the brand reputation as the most vigorous intensity (β =0.501, t= 11.088 at p = 0.000) and brand recognition with the lowest intensity (β =0.247, t= 4.3856 and p = 0.000) for p < 0.001). These results confirmed that the adoption of CSR had a positive impact on brand reputation, equity, awareness, and recognition. The research concluded that CSR significantly impacted brand management, which is crucial for start-ups.
Keywords: CSR; BRANDING; STARTUPS